Birds as bio-indicators and as tools to evaluate restoration measures - Roché, Jean (2012)
Within the RIPIDURABLE Project*, birds were used to characterize ecosystems*, to monitor environmental changes and to assess results of restoration measures. Bird surveys were carried out at different space and time scales using standardised point count methods on 8 watercourses in Portugal and France. Several aspects of riparian breeding bird community variation were assessed: along a decreasing gradient of vegetation complexity, along and upstream-downstream gradient, with different surrounding landscapes, with time, with management status, with time and management status, before and after river rehabilitation. Birds appear to be new and reliable indicators for assessing restoration of riparian ecosystems, complementary to those traditionally used.